Unified series solution for thermal vibration analysis of composite laminated joined conical-cylindrical shell with general boundary conditions. (September 2022) - Zuo, Peng; Shi, Xianjie; Ge, Renwei; Luo, Jingrun
Abstract: We establish a unified series solution for the free, steady-state, and transient vibration analysis of composite laminated joined conical–cylindrical shells under thermal environment. Additionally, artificial spring technology was used to deal with the general boundary conditions and continuity conditions for the common edge of the joined conical–cylindrical shell. The spectro-geometric method (SGM) and the first-order shear deformation theory (FSDT) were employed to derive the dynamic equation of motion. Subsequently, the displacement admissible functions were expressed in a general form comprising the Fourier sine and cosine terms to manipulate the arbitrary boundary conditions without pre-satisfying them. Moreover, the convergence and solution efficiency of the proposed approach was demonstrated by comparison with the finite element method solution. Furthermore, the influence of critical factors on the vibration behaviors of the coupled shells was investigated, with findings that would aid in their structural design. Highlights: Vibration characteristics of composite laminated-joined conical–cylindrical shell are presented. Employed spectrogeometric method based on first-order shear deformation theory. Convergence and solution efficiency of proposed approach verified with comparisons. Determined critical factors of free and forced vibration behaviors of such shells.